237-245 Beacon Street, 1868 - Unknown (Tufts Archival Research Center, 2005)
Street-level view of (left to right) 237-245 Beacon Street, between Clarendon Street to the east and Dartmouth Street to the west. The vine-covered facades of the four houses face northwest toward the Charles River. Only a partial view of the facade of 237 Beacon Street is included in the photograph. Copyprint; 241 Beacon Street owned by Julia Ward Howe from ca. 1887-1915. Architect H. Whitwell 7 1/4 x 8 11/16 Photographs